Comparison of Archaeal and Bacterial Diversity in Methane Seep Carbonate Nodules and Host Sediments, Eel River Basin and Hydrate Ridge, USA - Mason, Olivia U; Case, David H; Naehr, Thomas H; Lee, Raymond W; Thomas, Randal B; Bailey, Jake V; Orphan, Victoria J (MICROBIAL ECOLOGY, 2015)
Anaerobic oxidation of methane (AOM) impacts carbon cycling by acting as a methane sink and by sequestering inorganic carbon via AOM-induced carbonate precipitation. These precipitates commonly take the form of carbonate nodules that form within methane seep sediments. The timing and sequence of nodule formation within methane seep sediments are not well understood. Further, the microbial diversity associated with sediment-hosted nodules has not been well characterized and the degree to which nodules reflect the microbial assemblage in surrounding sediments is unknown. Here, we conducted a comparative study of microbial assemblages in methane-derived authigenic carbonate nodules and their host sediments using molecular, mineralogical, and geochemical methods. Analysis of 16S rRNA gene diversity from paired carbonate nodules and sediments revealed that both sample types contained methanotrophic archaea (ANME-1 and ANME-2) and syntrophic sulfate-reducing bacteria (Desulfobacteraceae and Desulfobulbaceae), as well as other microbial community members. The combination of geochemical and molecular data from Eel River Basin and Hydrate Ridge suggested that some nodules formed in situ and captured the local sediment-hosted microbial community, while other nodules may have been translocated or may represent a record of conditions prior to the contemporary environment. Taken together, this comparative analysis offers clues to the formation regimes and mechanisms of sediment-hosted carbonate nodules.
Keywords: HOV Alvin (Human Occupied Vehicle)